2020
DOI: 10.1177/0886260520912596
|View full text |Cite
|
Sign up to set email alerts
|

Medical Marijuana Dispensaries and Referrals for Child Maltreatment Investigations

Abstract: The changing legal status of marijuana in the United States has increased access to the drug through medical marijuana dispensaries. Limited research exists that examines the effects of these dispensaries on social problems including child maltreatment. The current study examines how medical marijuana dispensaries may affect referrals for child abuse and neglect investigations. Data are analyzed from 2,342 Census tracts in Los Angeles County, California. Locations of medical marijuana dispensaries were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…We found that while alcohol outlet density and percent of the population in poverty both had a small effect on the outcome of child abuse, the measure of racial-ethnic diversity (Blau’s Index) was associated with about a four-fold increase of risk of child abuse substantiations. This echoes the findings of Klein and Merritt (2014), who found that neighborhood heterogeneity (as measured by the Blau’s Index) was a stable predictor of child maltreatment referrals across all subgroups studied (Klein & Merritt, 2014), a phenomenon that Freisthler and Kranich (2020) also found to exist in a similar study in Los Angeles (Freisthler & Kranich, 2020). To examine the effects of segregation on child maltreatment substantiations in Los Angeles over time, Barboza (2019) also included a diversity measure—the Black–White (B–W) interaction index—in examining the effects of environmental factors using Bayesian hierarchical spatial regression models.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We found that while alcohol outlet density and percent of the population in poverty both had a small effect on the outcome of child abuse, the measure of racial-ethnic diversity (Blau’s Index) was associated with about a four-fold increase of risk of child abuse substantiations. This echoes the findings of Klein and Merritt (2014), who found that neighborhood heterogeneity (as measured by the Blau’s Index) was a stable predictor of child maltreatment referrals across all subgroups studied (Klein & Merritt, 2014), a phenomenon that Freisthler and Kranich (2020) also found to exist in a similar study in Los Angeles (Freisthler & Kranich, 2020). To examine the effects of segregation on child maltreatment substantiations in Los Angeles over time, Barboza (2019) also included a diversity measure—the Black–White (B–W) interaction index—in examining the effects of environmental factors using Bayesian hierarchical spatial regression models.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies have also considered the built environment as containing potential accelerants to the manifestation of child abuse. Specifically, child physical abuse was positively associated with measures of neighborhood density of off-premise alcohol locations (Freisthler et al, 2004(Freisthler et al, , 2007Freisthler & Kranich, 2020) and medical marijuana dispensaries (Freisthler et al, 2015). The built environment has been found to have deceleration factors as well, with lower rates of child maltreatment found proximal to mental health and substance abuse services (Maguire-Jack & Klein, 2015) and licensed day care facilities (Klein, 2011), as well as a moderating effect of substance abuse services density on the positive relationship between alcohol availability and child maltreatment (Morton, 2013).…”
Section: Child Abuse and The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We found only two studies not based on parents' self‐reports. The first (Freisthler & Kranich, 2022) found no association between the geographical availability of cannabis and rates of child protection referrals. The second (Donohue et al, 2019) found a positive association between cannabis use and the risk of CAN.…”
Section: Introductionmentioning
confidence: 99%
“…Greater alcohol supply, as reflected in greater alcohol outlet densities or lower taxes on alcoholic beverages, appears to increase child abuse and neglect in the United States (Freisthler, 2004; Freisthler et al, 2007; Freisthler & Kranich, 2022; Markowitz et al, 2010, 2014; Markowitz & Grossman, 1998, 2000; Morton et al, 2014; Sen, 2006). More specifically, density of bars is related to higher rates of substantiated reports of child abuse and neglect (Freisthler, 2004) and entries into foster care (Freisthler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%